Compost enriched with effective microorganism and Bordeaux mixture on ginger bacterial wilt (Ralstonia solanaceurum) Epidemics in southwestern, Ethiopia - Merga Jibat Guji; Mulukan Asfaw (Food, Agriculture and Natural Resources - NETWORKS, 2022)
Ginger is one of the most widely cultivated spice grown in various cropping systems and locations throughout the southwestern Ethiopia. Bacterial wilt, caused by Ralstonia solanacearum, is one of the serious diseases of ginger in Ethiopia. Field experiments were conducted during 2019 and 2020 to assess effects of soil amendments on bacterial wilt development and epidemics at Tepi, southwestern Ethiopia. Three soil amendments practices: compost, effective microorganisms and Bordeaux mixture alone and in integration were evaluated. Treatments were arranged in a randomized complete block design with three replications. Compost at the rate of 7 ton/ha enriched with effective microorganisms and Bordeaux mixture treatment significantly reduced ginger bacterial wilt incidence, area under disease progress curve and disease progress rate. This treatment reduced bacterial wilt mean incidence up to 21.08 % as compared to untreated control plot. Compost at the rate of 7 ton/ha also slowed down epidemic progression of bacterial wilt and significantly reduced the disease parameters when effective microorganisms and Bordeaux mixture were integrated. The overall results indicated that integrated compost enriched with effective microorganisms and Bordeaux mixture was effective to slow down the epidemics of ginger bacterial wilt and sustain ginger production and productivity. Hence, integrated compost enriched with effective microorganisms and Bordeaux mixture along with other crop management systems are recommended to improve ginger production and productivity at southwestern Ethiopia and other similar ecologies.